A SYSTEMATIC-ACTIVE APPROACH TO FORMULASTING FUTURE PRIMARY SCHOOL TEACHERS' ECOLOGICAL CULTURE (British Journal of Global Ecology and Sustainable Development, 2024)
The paper discusses how to help future primary school teachers create an ecological culture by presenting a methodical, proactive approach. The systematic-activity method helps students improve their personal, social, and cognitive skills as well as their civic engagement and self-control. The global environmental issue that concerns people now is far more complicated. When human wrongdoing is committed without considering the inherent environmental rules that govern the earth, the results are swift and catastrophic for all of creation.